2006
DOI: 10.1186/cc4833
|View full text |Cite
|
Sign up to set email alerts
|

Untitled

Abstract: The use of pulmonary artery catheters (PACs) during cardiac surgery varies considerably depending on local policy, ranging from use in 5–10% of the patient population to routine application. However, as in other clinical fields, recent years have witnessed a progressive decline in PAC use. One of the reasons for this is probably the increasing use of transoesophageal echocardiograpy, even though careful analysis of the information provided by PAC and transoesophageal echocardiograpy indicates that the two tool… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
3
3
2

Relationship

0
8

Authors

Journals

citations
Cited by 57 publications
(11 citation statements)
references
References 36 publications
0
11
0
Order By: Relevance
“…However, despite attempts to select for PAC expertise through selection of high volume cardiac surgery hospitals with PAC use, this analysis of EHRs does not indicate the level of experience of the PAC provider, whether the PAC was correctly used, or if a patient’s treatment was informed by PAC readings, highlighting additional study limitations. Local hospital policies and economic considerations influence PAC use (Ranucci 2006 ), and lack of information about these variables is an additional limitation of our study. A further difference between the current and prior database analyses is our ability to use both coding and clinical parameters to capture outcome measures and better match study arms.…”
Section: Discussionmentioning
confidence: 99%
“…However, despite attempts to select for PAC expertise through selection of high volume cardiac surgery hospitals with PAC use, this analysis of EHRs does not indicate the level of experience of the PAC provider, whether the PAC was correctly used, or if a patient’s treatment was informed by PAC readings, highlighting additional study limitations. Local hospital policies and economic considerations influence PAC use (Ranucci 2006 ), and lack of information about these variables is an additional limitation of our study. A further difference between the current and prior database analyses is our ability to use both coding and clinical parameters to capture outcome measures and better match study arms.…”
Section: Discussionmentioning
confidence: 99%
“…Conversely, the value of pulmonary artery pressures, pulmonary artery occlusion pressure (PAOP), mixed venous oxygen saturation (SvO 2 ), and right heart volumes, some of the variables that can be uniquely assessed at the bedside of the critically ill patient with help of the PAC and right-sided thermodilution, remains hotly debated [ 13 - 15 , 20 ]. The patient population or circumstance that is most likely to benefit from pulmonary artery catheterization is, therefore, still being actively looked for [ 13 - 15 , 21 , 22 ].…”
Section: What Do We Have and What Can They Do?mentioning
confidence: 99%
“…Moreover, valuable information may be obtained with the additional use of a Swan-Ganz catheter [33,34,39]. According to Ranucci [44], first degree of diastolic dysfunction of the left ventricle is depicted as impaired relaxation, is usually observed just after discontinuation of cardiopulmonary bypass, and is often reversible (temporary). Second degree mimicking pseudo-normalization, is a more severe condition, which sometimes is an intermediate step towards, third degree of dysfunction which is characterized by a restrictive pattern.…”
Section: Introductionmentioning
confidence: 99%
“…An increased ratio (> 2) between E and A waves of transmitral flow, and a blunted systolic waveform of the pulmonary vein flow is present due to left atrial pressure [ 34 , 36 , 39 ]. It has been demonstrated that mitral and pulmonary vein flow indexes correlate with pulmonary capillary wedge pressure (PCWP) [ 44 , 45 ]. Therefore, additional measurement of PCWP by using a Swan-Ganz catheter may be in this phase useful in estimating the time course of diastolic dysfunction and the effect of therapeutic manipulations [ 44 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation